OXIDE LAYER CHARACTERIZATION OF AlMg2 CLADDING OF IRRADIATED U3Si2/Al FUEL WITH 4,8 gU/cm3 DENSITY - Juan Carlos Sihotang; Maman Kartaman Ajiriyanto; Ely Nurlaily; Junaedi Junaedi; Aslina Br. Ginting (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2022)
OXIDE LAYER CHARACTERIZATION OF AlMg2 CLADDING OF IRRADIATED U3Si2/Al FUEL WITH 4,8 gU/cm3 DENSITY. To investigate the performance of AlMg2 cladding in the U3Si2/Al dispersion fuel, oxide layer characterization of AlMg2 cladding of the irradiated U3Si2/Al fuel with 4.8 gU/cm3 density was conducted. The oxide layer  on the surface of AlMg2 cladding is one of the changes that occur on the cladding after the U3Si2/Al fuel plate has been irradiated in the RSG-GAS reactor to a burn-up of ∼40%. The characterization and observation of the oxide layer was conducted using SEM (Scanning Electron Microscope) and Energy-dispersive X-ray spectroscopy (EDS). Samples with a size of 3x3 mm were taken from the middle of the fuel plate (middle position). After cutting, metallographic preparation includes mounting, grinding, polishing, and ultrasonic cleaning. SEM preparation was carried out by sputter coating using Au layer. The oxide layer on the AlMg2 cladding has a thickness of 10.3 µm with a uniformly distributed cracks along the oxide layer.Keyword: LEU, uranium-silicide, post-irradiation examination, AlMg2 cladding, oxide layer.